Biosorption of Uranium from Aqueous Solution by Reference and Indigenous Strains of Live Aspergillus.niger - S Sana; R Roostaaazad; S Yaghmaei (مجله علوم و فنون هسته‌ای, 2014)
The biosorption characteristics of uranium(VI) on reference and indigenous strains of live A.niger were evaluated. The influences of pH (3.0-7.0), biomass concentration (0.05-0.5 g dry biomass /100mL), initial uranium concentration (10-500mg/L), and contact time(30-1440 minutes) were investigated. In order to determine the residual concentration of metal, inductive coupled plasma spectrometry was used. The results indicate that the maximum biosorption of U on reference and indigenous biomass occur at pH=5 as 82.30% and 74.19%, respectively. The biosorption equilibrium was established in 60 and 120 minutes for reference and indigenous biomasses, respectively. The maximum biosorption was observed at a concentration 0.2 g dry biomass/100 mL for both biomasses. The maximum biosorption capacity of U was developed at an initial concentration of uranium 500mg/L as 105 and 143.5 mgU/g dry biomass for reference and indigenous biomasses, respectively. The adsorption process of reference and indigenous live A.niger could be well-defined by Langmuir isotherm with R2 values of 0.9972 and 0.9979, respectively. The obtained results indicated that the reference strain of live A.niger is more efficient for biosorption of U from aqueous solution in comparison with indigenous strain.